Digital Marketing and Direct Marketing in Shaping Purchase Decisions: The Mediating Effect of Brand Awareness - Della Stephanie Prawesti (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Digital technology development has led to significant changes in marketing communication strategies within the highly competitive cosmetics industry. Digital marketing and direct marketing have become key approaches used by companies to build consumer relationships and influence purchasing decisions. Objective: This study aims to analyze the influence of digital marketing and direct marketing on purchase decisions of Make Over products. Methods: This research adopts a quantitative causal associative design. Data were collected via structured questionnaires from 160 Make Over consumers in Jakarta. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: Digital marketing has a positive and significant effect on both brand awareness (β = 0.599, t = 10.546, p = 0.000) and purchase decisions (β = 0.532, t = 8.299, p = 0.000). Brand awareness significantly mediates the digital marketing–purchase decision relationship (indirect effect = 0.118, t = 2.266, p = 0.024), confirming partial mediation. In contrast, direct marketing does not significantly influence brand awareness (β = 0.078, t = 0.823, p = 0.411) or purchase decisions (β = 0.151, t = 1.844, p = 0.065), and brand awareness does not mediate the direct marketing–purchase decision path (indirect effect = 0.015, t = 0.750, p = 0.453). Brand awareness itself positively and significantly affects purchase decisions (β = 0.196, t = 2.414, p = 0.016). Conclusion: Digital marketing is the primary driver of both brand awareness and purchase decisions for Make Over products, while direct marketing demonstrates no statistically significant effect in this context.